CONCEPT AND PROCESS OF CREATING THE DANCE FILM "DEPRESSION" - Asmawardhana, Moh. Tegar Fajar; M.Sn, Drs. Bambang Sugito (Solah, 2023)
The Depresi dance work is a work that departs from personal experience. The phenomenon raised in this dance work often occurs in family relationships, namely broken homes which have an impact on mental disorders in children due to inharmonious parental relationships. This work chooses to focus on expressing motion symbols in people who are depressed, as well as highlighting depressive behaviors due to the impact of parental relationships. So that it causes children to lose interest in various things through the form of dance film performances using the type of dramatic dance. It is hoped that this dance work can be appreciated by the audience and connoisseurs so that they can find out about children who are experiencing depression. This dance work has a message conveyed to the audience that each child can overcome their trauma in their own way. Children who are depressed should not drag on in sadness. As a parent, you must be able to maintain the child's behavior in the problems you face. So that the child is not depressed and does not have excessive mental burden. In the process of the dance work, Depresi uses the theory from Jacqueline Smith about choreography, elasticity, and staccato which helps in realizing the concept in a dance film. As a choreographer, interpreting this phenomenon is done through a creation process, namely exploration, improvisation, composition, analysis, evaluation and finishing. The delivery of dance works through motion symbols in the exploration process as well as references to the stylist's experience are poured into dance films using cinematography. Visualization of children who experience trauma or depression is interpreted through symbols of motion and reveals solutions in healing depression to achieve peace in their life experiences. Dance film works that visualize depression can be observed through the curves of body movements. When the process of creating the motion that appears is a real memory in everyday life as an incident experienced by the choreographer. So that the condition of describing depression has an impact that appears and influences a person's psychological condition.